DINAMIKA PERAN KELUARGA DALAM PENCEGAHAN STUNTING: ANALISIS KUALITATIF PADA KELUARGA BERPENDAPATAN RENDAH DI KAWASAN URBAN - Sri Wahyuni; Dewi Setiyawati (Poltekkes Kemenkes Medan, 2023)
This study aims to analyze the role of families in preventing stunting among low-income families in urban areas. The research methodology employed was qualitative analysis, gathering data through in-depth interviews and participatory observation. The study participants consisted of low-income families with toddlers in urban areas. The findings reveal that families play a significant role in preventing stunting. The role of mothers is particularly crucial in providing exclusive breastfeeding, ensuring balanced dietary intake, and providing proper care. Social support from family and the community also plays a vital role in stunting prevention. Social-cultural factors such as eating norms, nutritional knowledge, accessibility to nutritious food, and the family environment influence eating behaviors and child care practices. Therefore, efforts to increase nutritional knowledge and awareness, improve accessibility to nutritious food, and strengthen the family's role are necessary to prevent stunting in urban areas, especially among low-income families.